004 Samelisant (SUVN-G3031), Differentiating features over current treatments of narcolepsy. (3rd May 2021) - Shinde, Anil; Subramanian, Ramkumar; Palacharla, Raghava; Benade, Vijay; Abraham, Renny; Kamuju, Venkatesh; Pandey, Santosh; Badange, Rajesh; Achanta, Pramod Kumar; Nirogi, Ramakrishna
Abstract: Introduction: Majority of pharmacological agents used in the treatment of narcolepsy have several limitations. Both nonclinical and clinical evidences suggest usefulness of the histamine H3 receptor (H3R) inverse agonists for the treatment of narcolepsy addressing several of the current limitations. Methods: Extensive nonclinical studies were carried out for Samelisant (SUVN-G3031) and other pharmacological agents that are currently being used for the treatment of narcolepsy. The nonclinical parameters like inter-species binding affinity, selectivity profile, in vivo and in vitro ADME features, nonclinical efficacy, neurochemistry and safety were compared. Results: Samelisant has no inter-species variation in binding affinity at H3R with less than 50% inhibition at 1 µM against 70 other targets. Unlike pitolisant, Samelisant has no significant binding affinity at sigma 1 and 2 receptor. Samelisant has no inhibition and induction liability towards major CYP enzymes and transporters. Pitolisant is reported to be a CYP3A4, CYP2B6, and CYP1A2 inducer and a CYP2D6 and OCT1 inhibitor. Samelisant has robust wake promoting effects. Samelisant showed negligible affinity towards hERG channel with IC50 > 10 µM and had no effects on heart rate or ECG parameters in dog telemetry study. Samelisant did not show convulsion in rats up to the tested dose of 100 mg/kg, p.o. Most of the pharmacological agents used for the treatment of narcolepsy have abuse liability; Samelisant produced no change in the striatal and accumbal dopamine levels in rats suggesting no propensity to induce abuse liability. Unlike competing H3R inverse agonists, Samelisant has no effects on fertility and embryo-fetal development up to the highest tested doses. Conclusion: Nonclinical studies demonstrated superiority of Samelisant over pharmacological agents used in the treatment of narcolepsy. Samelisant is currently being evaluated in a Phase 2 study as monotherapy for the treatment of narcolepsy with and without cataplexy (ClinicalTrials.gov Identifier: NCT04072380). Support (if any):